Isomer ratios and mean angular momenta of photonuclear reaction products - Bezshyyko, O.A.; Golinka-Bezshyyko, L.O.; Kadenko, I.M.; Mazur, V.M.; Plujko, V.A.; Strilchuk, N.V.; Vishnevsky, I.M.; Zheltonozhsky, V.A. (Вопросы атомной науки и техники, 2005)
Isomer ratios and mean angular momenta are obtained both for photofission products of
237Np, 238U and for nuclei
122,120m,gSb and 117m,gIn. Photonuclear reactions
121Sb(γ,n)120m,gSb, 123Sb(γ,n)122m,gSb, 118Sn(γ,p)117m,gIn were studied in
the last cases. The technique of gamma-ray spectrometry for isomeric ratio determination was used. Target nuclei
were irradiated by bremsstrahlung spectrum of microtron M-30. Comparison of isomer ratios calculated by Empire II
code with experimental data was performed. Effects of the nuclear structure model parameters on values of isomer
ratios are discussed Досліджено ізомерні відношення та визначено середні кутові моменти для продуктів фотоділення ядер 238U і 237Np, а також виміряні ізомерні відношення для ядер 120,122m,gSb и 117m,gIn в реакціях (γ,n) та (γ,p). Опромінення проводилося гальмівними γ-квантами мікротрону М-30 з максимальною енергією спектру 16 та 15 МеВ. Досліджено залежності ізомерних відношень від кутових моментів збуджених ядер з використанням програми Empire II для розрахунку характеристик ядерних реакцій. Измерены изомерные отношения и извлечены средние угловые моменты для продуктов фотоделения ядер 238U и 237Np, а также измерены изомерные отношения для ядер 120,122m,gSb и 117m,gIn в реакциях (γ,n) и (γ,p). Облучение проводилось тормозными γ-квантами микротрона М-30 с максимальной энергией спектра 16 и 15 МэВ. Исследованы зависимости изомерных отношений от угловых моментов возбужденных ядер с использованием программы Empire II для расчета характеристик ядерных реакций.